The Role Singapore Tourism Board (STB) Plays in Tourism Policy and Planning-Tourism Industry Stakeholder’s Perspectives - Chan, Kun-Chian (2009)
This research discusses the roles Singapore Tourism Board (STB) plays in tourism policy and planning from the tourism industry stakeholder’s perspectives. The author conducted interviews with one of the tourism industry stakeholders- travel agency. The finding shows that there are three main roles of STB- enthusiast, decision maker, and dictator in tourism policy and planning . Moreover, the political and social background of Singapore contribute to the main reasons why Singapore can successfully employ the “top-down” approach that no longer exists in most developed countries. Some suggestions are given to STB for the future development in tourism policy and planning, which include provision of more direct and transparent communication channel to the industry stakeholder, the equal respect for each industry member, and release of the control over the tourism market.